What Chefs Want When Buying Australian Seafood - Lawley, M.; Howieson, Janet (Routledge, 2015)
The food service sector is a significant sector of the food industry and yet little research has considered how and why chefs make purchasing decisions. This article explores how and why chefs make purchasing decisions for seafood to provide a basis from which the various stakeholders involved in seafood, fishers, farmers, and wholesalers can improve their business operations. Interviews were conducted with 68 chefs from three major cities in Australia. Results indicate that chefs purchase from multiple suppliers, with key drivers being consistency of quality and supply. Suppliers act as double gatekeepers, with little information going from chefs to producers and vice versa. Based on the findings, strategies are posited for both producers and wholesalers to better serve the food service sector.